Implications of Government Regulation Number 34 of 2021 Concerning the Use of Foreign Workers for Local Workers in South Tapanuli Regency in Siyasah Perspective - Raja Loya Jirga Raja Loya Jirga; Irwansyah Irwansyah (Law Development Journal, 2023)
This law research aims to find out what the government's policy is regarding the use of foreign workers according to Government Regulation Number 34 of 2021, find out what the policies are for the benefit of foreign workers in the South Tapanuli district, and examine what is the implications of using foreign workers for local workers, concerning needs for professional experts and the need for technologies that help work processes more effectively and efficiently. The research method used in this writing is a juridical-empirical one that is descriptive-analytical, namely the author explains systematically concerning the facts with their implementation process, which is supported by data obtained from the South Tapanuli Regency Manpower Office, then analyzed by describing word for word systematically to find answers to problems.